151k views
1 vote
Which option is correct and how would one solve for it?

Which option is correct and how would one solve for it?-example-1
User SeanC
by
4.8k points

2 Answers

2 votes

━━━━━━━☆☆━━━━━━━

▹ Answer

102

▹ Step-by-Step Explanation

Convert the notation into a sum and substitute values from 1-4:

(3¹⁻¹ *(1 - 1)) + (3²⁻¹ * (2 - 1)) + (3³⁻¹ * (3 - 1)) + (3⁴⁻¹ * (4 - 1))

0 + 3 + 18 + 81

= 102

Hope this helps!

CloutAnswers ❁

━━━━━━━☆☆━━━━━━━

User Egremont Of Yorke
by
4.9k points
2 votes

Answer:

102

Explanation:

We have the sum for k = 1 to 4 of 3 ^ ( k-1) * ( k-1)

k =1 3 ^ (1-1) * ( 1-1) = 3^0 * 0 = 0

k =2 3 ^ (2-1) * ( 2-1) = 3^1 * 1 = 3

k =3 3 ^ (3-1) * ( 3-1) = 3^2 * 2 = 9*2 = 18

k =4 3 ^ (4-1) * ( 4-1) = 3^3 * 3 = 27 *3 = 81

Add these together

0+3+18+81 =102

User Lidqy
by
5.2k points